High-entropy oxide coated lithium cobalt oxide positive electrode material and preparation method thereof
By coating the lithium cobalt oxide with high entropy oxide, the problem of insufficient magnification performance of lithium cobalt oxide positive electrode material in the prior art is solved, and the effect of significantly improving the material magnification performance, discharge capacity and cycling performance is achieved.
Patent Information
- Application Number
- CN202411597108.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The rate performance of lithium cobalt oxide cathode material in the prior art has not yet met the demand of new consumer electronics for high-performance batteries.
The lithium cobalt oxide material is sintered and coated by high-entropy oxide to form a lithium cobalt oxide positive electrode material with lithium cobalt oxide as the core and a high-entropy oxide as the coating layer. The chemical formula of the high entropy oxide is MOx, where M contains at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si.
The rate performance, discharge capacity and cyclic performance of lithium cobalt oxide cathode material are significantly improved, and the electrochemical performance of the material is enhanced.
Smart Images

Figure CN119480979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and particularly to a lithium cobalt oxide cathode material coated with high-entropy oxide and a preparation method thereof. Background Art
[0002] In recent years, some new consumer electronics have developed rapidly, such as electronic cigarettes, drones, and model airplanes. These application scenarios have put forward higher requirements for the rate performance of lithium cobalt oxide cathode materials.
[0003] Although in the prior art, the performance of the material is improved by coating lithium cobalt oxide with an oxide. For example, the invention patent 202310542447.0, "Porous alumina-doped titanium dioxide nanotube-coated lithium cobalt oxide composite material and its preparation method, lithium ion battery" discloses a porous alumina-doped titanium dioxide nanotube-coated lithium cobalt oxide composite material and its preparation method. The preparation method of the porous alumina-doped titanium dioxide nanotube-coated lithium cobalt oxide composite material includes the following steps: preparing TiO2 nanotubes doped with Al-MOF precursors by a solvothermal method, and then calcining them to obtain porous Al2O3-doped TiO2 nanotubes; mixing the porous Al2O3-doped TiO2 nanotubes and the lithium cobalt oxide material evenly, and obtaining a porous Al2O3-doped TiO2 nanotube-coated lithium cobalt oxide composite material after high-temperature treatment. This composite material has excellent electrochemical performance, making the LiCoO2 battery with it as the positive electrode active material have excellent discharge specific capacity, mass energy density, and cycle stability. However, the improvement of the performance of the lithium cobalt oxide cathode material is not obvious. Summary of the Invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a lithium cobalt oxide cathode material coated with high-entropy oxide and a preparation method thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: a lithium cobalt oxide cathode material coated with high-entropy oxide, the lithium cobalt oxide cathode material coated with high-entropy oxide includes lithium cobalt oxide located inside the material and a coating layer coated on the surface of the lithium cobalt oxide. The chemical formula of the lithium cobalt oxide located at the core is LiCo a Tm 1-a O2, where 0.99 ≤ a ≤ 0.999, and Tm is at least one of Mg, Al, Ti, Sr, Zr, Mo, and Nb; the coating layer is a high-entropy oxide coating layer, and the chemical formula of the high-entropy oxide is MO x , where M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si, 1 < x < 2 and satisfies that the total valence is zero.
[0006] The high entropy oxide coated lithium cobalt oxide positive electrode material is sintered and coated with the lithium cobalt oxide material by the high entropy oxide to form a lithium cobalt oxide positive electrode material with the lithium cobalt oxide material as the core and the high entropy oxide as the coating layer. The chemical formula of the high entropy oxide is MO x , wherein M contains at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si, which can not only improve the discharge capacity and cycle performance of the lithium cobalt oxide positive electrode material, but also significantly improve the rate performance of lithium cobalt oxide.
[0007] Preferably, the chemical formula of the high entropy oxide is MO x , wherein M contains at least 6 of Fe, Co, Ni, Mn, Al, Cr, and Si.
[0008] Preferably, the chemical formula of the high entropy oxide is MO x , wherein M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si and must include Si.
[0009] Through research, the inventors found that when a lithium cobalt oxide positive electrode material is formed by a high entropy oxide as a coating layer of the lithium cobalt oxide material and contains Si in the coating layer, the high entropy oxide combined with other components can better improve the discharge capacity, cycle performance and rate performance of the lithium cobalt oxide positive electrode material.
[0010] Preferably, the chemical formula of the high entropy oxide is MO x , wherein M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si and must include Si, Fe, Co, and Ni.
[0011] The inventors have discovered through research that the combination of the above elements of high entropy oxide can better improve the discharge capacity, cycle performance and rate performance of lithium cobalt oxide positive electrode materials.
[0012] Preferably, the chemical formula of the high entropy oxide is MO x , wherein M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si and must include Fe, Co, Ni, Mn, Al, and Si.
[0013] The inventors have discovered through research that the combination of the above elements of high entropy oxide can better improve the discharge capacity, cycle performance and rate performance of lithium cobalt oxide positive electrode materials.
[0014] Preferably, the coating layer has a thickness of 1 nm to 500 nm.
[0015] Preferably, the coating layer has a thickness of 5 nm to 100 nm.
[0016] Preferably, the content of the coating layer in the high entropy oxide-coated lithium cobalt oxide positive electrode material is 0.1% to 1%.
[0017] The present invention also provides a method for preparing any of the above-mentioned high entropy oxide-coated lithium cobalt oxide positive electrode materials, the method comprising the following steps:
[0018] (1) The lithium source, the cobalt source, and the Tm source are weighed and mixed in the required stoichiometric ratio and then subjected to the first heat treatment to obtain the lithium cobalt oxide matrix material LiCo a Tm 1-a O2; the holding temperature of the first heat treatment is 940℃~1000℃, the holding time is 8~16 hours, the heating rate is 3~5℃ / min, and the sintering atmosphere is air;
[0019] (2) Lithium cobalt oxide matrix material and MO x The source materials are mixed uniformly according to the mass ratio and then subjected to a second heat treatment to obtain a high entropy oxide-coated lithium cobalt oxide positive electrode material; the second heat treatment has a holding temperature of 750°C to 850°C, a holding time of 6 to 12 hours, a heating rate of 3 to 5°C / min, and an air sintering atmosphere.
[0020] Preferably, the lithium source is one or both of lithium carbonate and lithium hydroxide; the cobalt source is one or both of its oxide and carbonate and the particle size of the cobalt source satisfies 3.5μm≤D50≤5.5μm; the Tm source is one or more of its oxide, hydroxide and carbonate.
[0021] Preferably, the M source is a nano-oxide of a corresponding element and the particle size satisfies D50≤2.0 μm.
[0022] The present invention also provides a lithium ion secondary battery, which comprises any of the above-mentioned high entropy oxide-coated lithium cobalt oxide positive electrode materials.
[0023] The beneficial effect of the present invention is that the present invention provides a high entropy oxide coated lithium cobalt oxide positive electrode material and a preparation method thereof. The high entropy oxide coated lithium cobalt oxide positive electrode material of the present invention is sintered and coated with a high entropy oxide on a lithium cobalt oxide material to form a lithium cobalt oxide positive electrode material with a lithium cobalt oxide material as a core and a high entropy oxide as a coating layer, and the chemical formula of the high entropy oxide is MO x, wherein M comprises at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si, which can not only improve the discharge capacity and cycle performance of the lithium cobalt oxide positive electrode material, but also significantly improve the rate performance of lithium cobalt oxide. The advantages of the high entropy oxide coated lithium cobalt oxide positive electrode material of the present invention are: 1. The nanoscale high entropy oxide coating layer can construct a lithium ion fast channel on the surface of the lithium cobalt oxide matrix, thereby greatly improving the rate performance of the material. 2. The nanoscale high entropy oxide coating layer can form a dense layer on the surface of the lithium cobalt oxide matrix, isolating the direct contact between the electrolyte and the matrix material, thereby reducing side reactions. And the selection of the type of high entropy oxide material improves the first coulomb efficiency and reduces the consumption of active lithium, thereby ensuring excellent capacity utilization and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 TEM image of the high entropy oxide-coated lithium cobalt oxide positive electrode material according to an embodiment of the present invention.
[0025] Figure 2 HRTEM image of the high entropy oxide-coated lithium cobalt oxide positive electrode material according to an embodiment of the present invention.
[0026] Figure 3 Graph showing cycle retention rates of some embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Example 1
[0029] As a high entropy oxide coated lithium cobalt oxide positive electrode material of an embodiment of the present invention, the high entropy oxide coated lithium cobalt oxide positive electrode material includes lithium cobalt oxide located inside the material and a coating layer coated on the surface of the lithium cobalt oxide, and the chemical formula of the lithium cobalt oxide located in the core is LiCo 0.9935 Mg 0.003 Ti 0.003 Sr 0.0002 Mo 0.0003 O2. The coating layer is a high entropy oxide coating layer, and the chemical formula of the high entropy oxide is MO x , wherein M includes Fe, Co, Ni, Mn, Al, Cr, Zn, and Si.
[0030] The method for preparing the high entropy oxide-coated lithium cobalt oxide positive electrode material of the embodiment of the present invention comprises the following steps:
[0031] (1) Lithium carbonate, cobalt oxide, magnesium hydroxide, titanium dioxide, molybdenum dioxide, and strontium carbonate were weighed in stoichiometric proportions to prepare LiCo 0.9935 Mg 0.003 Ti0.003 Sr 0.0002 Mo 0.0003 O2. After mixing all the raw materials evenly, keep them at 955 °C for 12 h, with a heating rate of 4 °C / min and a sintering atmosphere of air;
[0032] (2) Weigh the lithium cobalt oxide material obtained in step (1) and nano-iron oxide, nano-cobalt ferrite, nano-nickel oxide, nano-manganese ferrite, nano-aluminum oxide, nano-chromium oxide, and nano-silicon dioxide in proportion to prepare lithium cobalt oxide material @0.1% (Fe 0.1 Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 Cr 0.1 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero;
[0033] After mixing all the raw materials evenly, keep them at 820 °C for 9 h. The heating rate is 3 °C / min and the sintering atmosphere is air. 0.1% means (Fe 0.1 Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 Cr 0.1 O x ) 0.5 ·(SiO2) 0.5 , that is, the mass content of the high-entropy oxide in the high-entropy-oxide-coated lithium cobalt oxide cathode material.
[0034] Example 2
[0035] As a high-entropy-oxide-coated lithium cobalt oxide cathode material according to an embodiment of the present invention, the only difference between this example and Example 1 is that the mass content of the high-entropy oxide in the high-entropy-oxide-coated lithium cobalt oxide cathode material is 0.5%.
[0036] Example 3
[0037] As a high-entropy-oxide-coated lithium cobalt oxide cathode material according to an embodiment of the present invention, the only difference between this example and Example 1 is that: the mass content of the high-entropy oxide in the high-entropy-oxide-coated lithium cobalt oxide cathode material is 1%.
[0038] Example 4
[0039] As a high-entropy-oxide-coated lithium cobalt oxide cathode material according to an embodiment of the present invention, the only difference between this example and Example 1 is that: the mass content of the high-entropy oxide in the high-entropy-oxide-coated lithium cobalt oxide cathode material is 0.5%, and the high-entropy oxide is (Fe 0.1 Co0.2 Ni 0.2 Mn 0.2 Al 0.2 Zn 0.1 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0040] Example 5
[0041] As a lithium cobalt oxide cathode material coated with a high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Example 4 is: (Fe 0.1 Co 0.2 Ni 0.2 Mn 0.1 Al 0.3 Zn 0.1 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0042] Example 6
[0043] As a lithium cobalt oxide cathode material coated with a high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Example 4 is: the high-entropy oxide is (Fe 0.1 Co 0.3 Ni 0.1 Mn 0.1 Al 0.3 Zn 0.1 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0044] Example 7
[0045] As a lithium cobalt oxide cathode material coated with a high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Example 4 is: the high-entropy oxide is (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0046] Example 8
[0047] As a lithium cobaltate cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 Zn 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0048] Example 9
[0049] As a lithium cobaltate cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Fe 0.2 Co 0.2 Ni 0.2 Al 0.2 Cr 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0050] Example 10
[0051] As a lithium cobaltate cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Fe 0.2 Co 0.2 Mn 0.2 Al 0.2 Zn 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0052] Example 11
[0053] As a lithium cobaltate cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Fe 0.2 Co 0.2 Ni 0.2 Al 0.2 Zn 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0054] Example 12
[0055] As a lithium cobalt oxide cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Fe 0.2 Mn 0.2 Ni 0.2 Al 0.2 Cr 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0056] Embodiment 13
[0057] As a lithium cobalt oxide cathode material coated with high-entropy oxide according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 4 is that the high-entropy oxide is (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0058] Comparative Example 1
[0059] As a lithium cobalt oxide cathode material coated with high-entropy oxide according to a comparative example of the present invention, the only difference between this comparative example and Embodiment 4 is that the high-entropy oxide is (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0060] Comparative Example 2
[0061] As a lithium cobalt oxide cathode material coated with high-entropy oxide according to a comparative example of the present invention, the only difference between this comparative example and Embodiment 4 is that the high-entropy oxide is (Fe 0.25 Co 0.25 Ni 0.25 Al 0.25 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0062] Comparative Example 3
[0063] As a lithium cobalt oxide cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is (Fe 0.25 Co 0.25 Al 0.25 Mn 0.25 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0064] Comparative Example 4
[0065] As a lithium cobalt oxide cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is (Fe 0.25 Al 0.25 Ni 0.25 Mn 0.25 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0066] Comparative Example 5
[0067] As a lithium cobalt oxide cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is (Al 0.25 Co 0.25 Ni 0.25 Mn 0.25 O x ) 0.5 ·(SiO2) 0.5 , where 1 < x < 2 and the total valence is zero.
[0068] Comparative Example 6
[0069] As a lithium cobalt oxide cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 Cr 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0070] Comparative Example 7
[0071] As a lithium cobalt oxide cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Co 0.2 Ni0.2 Mn 0.2 Al 0.2 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0072] Comparative Example 8
[0073] As a lithium cobalt oxide cathode material coated with a high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0074] Comparative Example 9
[0075] As a lithium cobalt oxide cathode material coated with a high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Co 0.2 Ni 0.2 Al 0.2 Cr 0.2 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0076] Comparative Example 10
[0077] As a lithium cobalt oxide cathode material coated with a high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Co 0.2 Mn 0.2 Al 0.2 Cr 0.2 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0078] Comparative Example 11
[0079] As a lithium cobalt oxide cathode material coated with a high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Fe 0.1 Ni 0.2 Mn 0.2 Al 0.2 Cr 0.2 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0080] Comparative Example 12
[0081] As a lithium cobaltate cathode material coated with high-entropy oxide as a comparative example of the present invention, the only difference between this comparative example and Example 4 is that the high-entropy oxide is Co 0.2 Ni 0.2 Mn 0.2 Al 0.2 Cr 0.1 Zn 0.1 O x , where 1 < x < 2 and the total valence is zero.
[0082] Experimental Method
[0083] I. Material Characterization
[0084] As Figure 1 is the TEM image of Example 6. It can be clearly seen from the figure that there is a continuous nano-coating layer on the surface of the matrix, and the thickness ranges from a few nanometers to several hundred nanometers. Figure 2 is the HRTEM image of Example 6. It can be clearly seen from the figure that the coating layer here is below 20 nm, continuous and dense, and the coating effect is good.
[0085] II. Electrochemical performance test uses a half-cell (3.0V - 4.3V), and the key parameters are as follows:
[0086] 1) Cathode material: SP:PVDF = 80:10:10
[0087] 2) Anode: Lithium foil
[0088] 3) Electrolyte: 1.0 M LiPF6 (DMC:EC:EMC = 1:1:1 Vol%)
[0089] The experimental results of the electrochemical performance are shown in Table 1.
[0090] Table 1 Performance of Lithium Cobaltate Cathode Material Coated with High-Entropy Oxide
[0091]
[0092]
[0093] From Table 1 and Figure 3 the results show that the lithium cobaltate cathode material coated with high-entropy oxide of the present invention is obtained by sintering and coating the lithium cobaltate material with high-entropy oxide, forming a lithium cobaltate cathode material with the lithium cobaltate material as the core and the high-entropy oxide as the coating layer. The chemical formula of the high-entropy oxide is MO x, wherein M contains at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si, which can not only improve the discharge capacity and cycle performance of the lithium cobalt oxide positive electrode material, but also significantly improve the rate performance of lithium cobalt oxide.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high entropy oxide coated lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide cathode material coated with high-entropy oxide includes lithium cobalt oxide inside the material and a coating layer coated on the surface of lithium cobalt oxide. The chemical formula of the lithium cobalt oxide at the core is LiCo a Tm 1-a O2, where 0.99 ≤ a ≤ 0.999, and Tm is at least one of Mg, Al, Ti, Sr, Zr, Mo, and Nb; the coating layer is a high-entropy oxide coating layer, and the chemical formula of the high-entropy oxide is MO x , where M contains at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si, 1 < x < 2 and the total valence is zero.
2. The high entropy oxide coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: Among them, M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si and must include Si.
3. The high entropy oxide coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: Among them, M includes at least 6 of Fe, Co, Ni, Mn, Al, Cr, Zn, and Si and must include Si, Fe, Co, and Ni.
4. The high entropy oxide coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The thickness of the coating layer is 1 nm to 500 nm.
5. The high entropy oxide coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The thickness of the coating layer is 5 nm to 100 nm.
6. The high entropy oxide coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The content of the coating layer in the high entropy oxide coated lithium cobalt oxide positive electrode material is 0.1% to 1%.
7. The method for preparing a high entropy oxide-coated lithium cobalt oxide positive electrode material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) The lithium source, the cobalt source, and the Tm source are weighed and mixed in the required stoichiometric ratio and then subjected to the first heat treatment to obtain the lithium cobalt oxide matrix material LiCo a Tm 1-a O2; the holding temperature of the first heat treatment is 940℃~1000℃, the holding time is 8~16 hours, the heating rate is 3~5℃ / min, and the sintering atmosphere is air; (2) Lithium cobalt oxide matrix material and MO x The source materials are mixed uniformly according to the mass ratio and then subjected to a second heat treatment to obtain a high entropy oxide-coated lithium cobalt oxide positive electrode material; the second heat treatment has a holding temperature of 750°C to 850°C, a holding time of 6 to 12 hours, a heating rate of 3 to 5°C / min, and an air sintering atmosphere.
8. The method for preparing a high entropy oxide-coated lithium cobalt oxide positive electrode material according to claim 7, characterized in that: The lithium source is one or both of lithium carbonate and lithium hydroxide; the cobalt source is one or both of its oxide and carbonate and the particle size of the cobalt source satisfies 3.5μm≤D50≤5.5μm; the Tm source is one or more of its oxide, hydroxide and carbonate.
9. The method for preparing a high entropy oxide-coated lithium cobalt oxide positive electrode material according to claim 7, characterized in that: The M source is a nano-oxide of a corresponding element and the particle size satisfies D50≤2.0 μm.
10. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises the high-entropy oxide-coated lithium cobalt oxide positive electrode material as claimed in any one of claims 1 to 6.
Citation Information
Patent Citations
High-entropy ceramic modified positive electrode material and preparation method and application thereof
CN115050940A
Layered lithium-rich manganese-based high-entropy positive electrode material, preparation method thereof and battery
CN115513449A
Doped high-voltage positive electrode material, synthesis method and application in sodium-ion battery
CN116666617A
High-entropy multi-metal oxide coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN118588905A
Lithium secondary battery and preparation method therefor
TW202431679A
Cited By
High-voltage high-rate lithium cobalt oxide positive electrode material and preparation method thereof
CN121416482A
Preparation method for regulating and controlling particle entropy distribution of lithium cobalt oxide positive electrode material and high-voltage lithium ion battery
CN121536973A